An Experimental Investigations for Improving Part Strength in Fused Deposition Modeling - Kumar Maurya, Nagendra; Rastogi, Vikas; Singh, Pushpendra (International Journal of Engineering and Technology, 2018)
This paper aims to experimentally investigate the impact of process parameter on ultimate tensile strength & rate of fabrication through fused deposition modeling. For this purpose MakerBot Replicator -2, 3D desktop printer was used for the fabrication of test samples. ASTM D638 standard was selected for the preparation of test specimen of poly lactic acid (PLA) material. The process parameters used in this investigation were layer thickness, raster angle, infill pattern and orientation. Experiment was conducted as per the Taguchi orthogonal design array (L16). Finally Gray relational analysis (GRA) was employed to select the optimum best level of process parameter. A regression model was developed in terms of process parameters. For checking the goodness of fit for the model, a confirmation test was conducted which reveals that developed model was good enough to predict the response in the CI of 95%. The optimum level of process parameters was found to be layer thickness of 0.1 mm, raster angle 450, honeycomb infill pattern and flat orientation.